Preparation and characterization of PLA/algae nanocomposites for packaging industry - Adli, Sarah Amalina; Ali, Fathilah; Azmi, Azlin Suhaida (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Recently, the accumulation of waste on landfill caused mainly by plastic packaging raises environmental concerns. Therefore, researchers have come up with biodegradable polymer to replace conventional plastic in the packaging industry. Now, many biopolymers have been studied and some of them shows potential to substitute petroleum based plastic, but one biopolymer (polylactic acid (PLA)) in particular stands out as it possesses the same properties as conventional plastic like polystyrene and polyester. However, PLA’s slow degradation rate and brittleness limit its application. Therefore the aim of this study is to modify PLA in order to overcome the limitations and broaden its application in the packaging industry. PLA is modified by using algae as a filler to lower the cost and improve degradation rate of PLA, whereas epoxidized palm oil (EPO) is used as plasticizer to enhance PLA’s flexibility. In this research, plasticized PLA (PLAEPO) is mixed using 5 wt% of algae filler content. The composite is prepared by two methods; solvent casting and melt mixing. For solvent casting the blends are dissolved in chloroform and casted by evaporation of solvent whereas in melt mixing method, the blends are melt blended using an internal mixer. Thermal, mechanical and morphological properties of PLAEPO/algae composite is conducted by using differential scanning calorimetry (DSC), tensile testing and scanning electron microscopy respectively. After further discussion and consideration, it is decided that PLAEPO/ALG-5 is best prepared by solvent casting method.